Build Your Own Solar Panel - Hurley, Phillip (Good Idea Creative Services, 2012)
Converting solar energy to electricity via photovoltaic cells is one of the most exciting and practical scientific discoveries of the last several hundred years. The use of solar power is far less damaging to the environment than burning fossil fuels to generate power. In comparison to other renewable energy resources such as hydro power, wind, and geothermal, solar has unmatched portability and thus flexibility. The sun shines everywhere. These characteristics make solar power a key energy source as we move away from our fossil fuel dependency, and toward more sustainable and clean ways to meet our energy needs.